دلالة التناص التراثي في الشعر العربي المعاصر - خطوي, العيفة; جعيرن, ميهوب (جامعة الوادي - University of Eloued, 2021)
ملخص : يعتبر التناص التراثي –كبنية جاهزة لها محمولاتها الدلالية– يتداخل مع النّص الشعري فيثري دلالته ويؤطر بنيته حسبما يفجره الشاعر وحسبما يتناوله وما يخلع عليه من توشجات وعلائق تتجاوز معه وتختمر في سياق نصي جديد يناط به ويولد شفراته ورموزه،فاحتلت بذلك كلمة (تراث) في الثقافة العربية مكانة مرموقة وذلك ما للتراث العربي بكافة أشكالهوأنواع من أهمية كبيرة، فهو ماضي الأمة العريق وأصالتها المشرقة، فقلما نجد إنسانا عربياً يتخلى عن تراثه ولا يفتخر به، لأن ذلك أمر ليس من شيمه، بل نجد أن العرب قد اهتموا بالتراث العربي اهتماماً كبيراً ،ووضعوه في ميزان حياتهم، وعملوا على توعيةالأجيالالجديدة بعراقة هدا التراث، وكان من أهم وسائل الاهتمام بالتراث العربي العمل على توظيفه في الأدب روايةً ومسرحا وشعرا، ونظرا لاحتلال الشعر المكانة الأبرز بین سائر ألوان الأدب الأخرى؛ فقد حظي الشعر العربي بشتى ألوان التراث، وأصبحت القصيدةالعربية تتغنى بالتراث في أحضان أبياتها، بل ويمكن لنا القول بأن جمال القصیدة العربیة أصبح يتوقف على قدرة استدعائها للتراث. وبما أن الشعر جزء لا يتجزأ من الشعر العربي فقد اعتنى ھو الآخر بالتراث بشكل وعمل على توظيفه مستخدما في ذلك وسائل متعددة لتتغنى القصیدة العربية المعاصرة بالتراث1. الكلمات المفتاحية: التناص ، التراث ، الشعر العربي المعاصر . Abstract The heritage intertwining - as a ready-made structure with its semantic implications - is considered tointerfere with the poetic text, enrichingits connotation and framing its structure according to what the poet detonates and as he deals with it and the interactions and relationships that he takes away from him and brewing in a new textual context entrusted with him and generating his blades and symbols, thus occupying the word (heritage) in the culture Arabic is a prominent place, and that is what the Arab heritage in all its forms and types is of great importance, for it is the nation’s ancient past and its bright originality, so hardly we find an Arab person who gives up his heritage and is not proud of it, because that is not a thing of his will, but we find that the Arabs have paid great attention to the Arab heritage Their life balance, and they worked to educate the new generations of the ancient heritage of this heritage, and one of the most important means of interest in Arab heritage was to employ itinliterature, with novels, theaterand poetry, given thatpoetry occupied the most prominent place among allother types of literature; Arabicpoetry received all kinds of heritage, and the Arabic poem became rich in heritage in the arms of its rituals. Indeed, we can say that the beauty of the Arabic poem now depends on its ability to summon the heritage. Since poetry is an integral part of Arabic poetry, it has also taken care of the heritage in a way and worked to employ it using various means to make the contemporary Arab poem sing the heritage Key words: intertextuality, heritage, contemporary Arabic poetry.
مقال
Keywords: التناص التراث الشعر العربي المعاصر